Levetiracetam as a first‐line antiseizure medication in WHO grade 2 glioma: Time to seizure freedom and rates of treatment failure. Issue 4 (23rd January 2023) - Fairclough, Sam; Goodden, John; Chumas, Paul; Mathew, Ryan; Maguire, Melissa
Abstract: Objective: The high seizure burden seen in World Health Association (WHO) grade 2 gliomas is well documented. This study aims to identify factors that influence the probability of seizure freedom (12 months of seizure remission) and treatment failure (antiseizure medication [ASM] cessation or introduction of an alternative) in patients with WHO grade 2 glioma. Methods: This is a retrospective observational analysis of patients from a regional UK neurosurgical center with histologically proven ( n = 146) WHO grade 2 glioma and brain tumor related epilepsy. Statistical analyses using both Kaplan‐Meier and Cox proportional hazards models were undertaken, with a particular focus on treatment outcomes when the commonly prescribed ASM levetiracetam ( n = 101) is used as first line. Results: Treatment with levetiracetam as a first‐line ASM resulted in a significant increase in the probability of seizure freedom ( p < .05) at 2 years compared with treatment with an alternative ASM. Individuals presenting with focal seizures without bilateral tonic‐clonic progression were between 39% and 42% significantly less likely to reach seizure freedom within 10 years ( p < .05) and 132% more likely to fail treatment by 5 years ( p < .01) when compared to individuals who had seizures with progression to bilateral tonic‐clonic activity. ASM choice did not significantly affect treatment failure rates. Significance: More than two‐thirds of patients with WHO grade 2 glioma related epilepsy treated with levetiracetam first line achieve seizure freedom within 2 years and it is a reasonable first‐choice agent. Experiencing mainly focal seizures without progression infers a significant long‐term reduction in the chance of seizure freedom. Further studies are needed to inform ASM selection.